Prevalence of escherichia coli and salmonella in fish and blood clam (anadara granosa) from wet markets and hypermarkets in Kuala Pilah / Fatin Batrisyia Johari, Nur Fatin Farhanah Zapri and Suwaibah Mohamed - Johari, Fatin Batrisyia; Zapri, Nur Fatin Farhanah; Mohamed, Suwaibah (UiTM Cawangan Negeri Sembilan, 2022)
Food poisoning is one of Malaysia's top five infectious illnesses, with Salmonella serovars as the most known infectious agent. Pathogenic microorganisms, particularly Salmonella and E. coli, have been detected in various seafood, mostly fish and clamps. Thus, this study aims to assess the prevalence and antimicrobial resistance of Salmonella and E. coli isolated from wild-caught raw fishes and blood clam (Anadara granosa) from wet markets and hypermarkets in Kuala Pilah Negeri Sembilan. A total of 15 fish were sampled from three hypermarkets. Meanwhile, 18 blood clams were sampled from three wet markets in Kuala Pilah, Negeri Sembilan. The surface of fish (skin, gills, and guts) and blood clam (inner, outer, and meat) were swabbed to isolate Salmonella and E. coli. The isolates were then identified based on their morphological characteristics, and further confirmation was done using a biochemical test. The assessment of bacterial resistance was conducted using an antibiotic susceptibility test involving seven antibiotics: tetracycline (30 µg), streptomycin (10 µg), nalidixic acid (30 µg), ciprofloxacin (5 µg), ampicillin (10 and 2 µg), chloramphenicol (30 µg), sulphamethoxazole/trimethoprim (25 µg) and Multiple antibiotic resistants (MAR). Findings showed that 6.7% (1/15) of isolates from fish samples tested positive for both bacteria. However, only 5.6% (1/18) of blood clam samples contained Salmonella. Most isolates were susceptible to antibiotics except for ampicillin, while MAR index results showed a value within 0.2 for both samples, indicating the samples had minimal exposure to antibiotics usage. In conclusion, the presence of Salmonella and E. coli in collected samples and their resistance to antibiotics may derive from contamination occurring in the natural aquatic environment, during processing, or due to unhygienic and improper handling. Therefore, effective control strategies should be implemented to prevent potential contamination, especially when handling and processing the fish and blood clam.